MAGNOLIOPHYTA (FLOWERING PLANTS): A LOGICAL AND PHYLOGENETIC CLASSIFICATION - M. DANIEL, (International Journal of Pharma and Bio Sciences, 2011)
All recent phylogenetic classifications of flowering plants are never field-oriented and thus the teacher and the taught find them difficult to understand and practise. Therefore a new student-friendly, yet phylogenetic system is proposed here. Since the spectacular diversification and related dominance of the flowering plants are primarily due to the flowers, especially to the petals, the apetalous taxa are grouped separate emerging parallel to the petaliferous taxa. In the present system, the Magnoliophyta (Angiosperms) are divided to two classes Magnoliopsida (Dicotyledonous plants) and Liliopsida Monocotyledonous plants). At the base of Magnoliopsida are the primitive subclasses Magnoliidae and apetalous Hamamelidae. The Caryophyllidae evolved from the latter subclass while the former gave rise to the subclasses Malvidae, Rutidae, Rosidae, and Ebenidae. The highly evolved subclasses, Lamiidae and Asteridae are derived from Ebenidae. The Liliopsida contain five subclasses with Alismatidae at the base from which evolved Cyperidae and Arecidae on one side and Zingiberidae and Liliidae on the other side. The evolutionary strategies and phylogeny of all these classes are also explained.